IMPLEMENTASI TEKNOLOGI AUGMENTED REALITY PADA BROSUR PENJUALAN MOBIL BERBASIS ANDROID DI PT. BOROBUDUR OTO MOBIL - Suhendra, Agung Aditya; Handayani, Irma (Direktorat Penelitian dan Pengabdian Masyarakat, Universitas Telkom, 2023)
PT Borobudur Oto Mobil, which is engaged in products or services, needs advertising media to inform the types of products or services offered. One of the advertising media is to use brochures as a car promotion media so that customers can get detailed information about cars, but brochure media still has shortcomings, namely customers cannot see the shape of the car, customers must come to the dealer directly to see the shape of the car offered. This research designs an application program by applying augmented reality technology that is implemented into an android-based car sales brochure. The brochure will have a marker that functions as a marker so that the 3D object that has been created will appear on the marker placed on the brochure. By using augmented reality technology, customers can directly see the 3D shape of the cars offered, and help employees in promoting Mitsubishi Xpander and Pajero car products. The results obtained from testing the Virtual Dealer application, the system in the application can function, where the application successfully displays 3D objects correctly above the marker, as well as features to zoom in, zoom out, change colors, play engine or horn sounds. Keywords:Augmented reality, brochure, mitsubishi, 3d, marker based-tracking, unity